Mixing processes and buoyancy transport in stratified turbulent flows - Petrolo, Diana (Università degli Studi di Parma. Dipartimento di Ingegneria e architettura, 2020)
This thesis attempts to increase the overall understanding of turbulent mixing by exploring the controls on the vertical buoyancy transport in a stratified turbulent Taylor-Couette flow. The inner cylinder of the tank, of radius R1, rotates, while the outer cylinder, of radius R2, is fixed, and the gap Δ R=R2-R1 is filled with fluid up to a depth H, so that the aspect ratio H/ Δ R=2.7-2.8. To simulate the global overturning circulation that perpetually carries and redistributes heat, salt and carbon between ocean basins at different rates, we conduct a series of experiments where we vary the rotation of the inner cylinder, Ω. In addition, we model rainfall and ice melting on the ocean surface by supplying a fresh water flux at the top of the tank, while the dense currents released by ice formation at the Antartica are modeled by a saline water flux supplied at the base of the tank. At the same time, we vent the same flux as the supply by two sinks located at the same depth of the respective sources. In our stylized experiments, the diapycnal mixing through isopycnal surfaces can be associated to the salt flux extracted at the top, whereas the upwelling flux can be measured by the fluid extracted at the bottom. In our experiments, we also vary the salinity of the bottom source, in order to simulate different interglacial periods. Firstly, we found that in the unsaturated regime, the vertical buoyancy flux is rate-limited by the salinity of the bottom source and it depends linearly on the buoyancy frequency, N, while in the saturated regime, it is rate-limited by turbulence, it is independent on N and proportional to Ω^3, matching the equivalent flux through a two-layer or multi-layer stratification, or through the interfaces that spontaneously form in a linear stratified fluid, for sufficiently high initial stratification. In this thesis, we will also discuss the influence of the initial condition and of the position of the sources and sinks on the steady-state stratification, as well as the ...